Putting on a tight leash and levelling playing field: An experiment in strategic obfuscation and consumer protection - Yiquan Gu; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
The paper reports the results of an experiment where asymmetric sellers of a product can obfuscate the market. We show that policy measures may have unintended effects of increasing obfuscation incentives. We find that policies that limit the effectiveness of obfuscation and policies that promote parity between firms can lead less prominent firms to increase their obfuscation efforts. Despite this unintended effect, however, the former type of policies is effective in boosting consumer welfare.
Keywords: C91; D18; D43; L13; 330; Experiment; Obfuscation; Consumer Protection; Behavioural Industrial Organisation